Trends in Sandeel Growth and Abundance off the East Coast of Scotland - MacDonald, Alan; Speirs, Douglas C.; Greenstreet, Simon P. R.; Boulcott, Philip; Heath, Michael R. (Frontiers in Marine Science, 2019)
Sandeels Ammodytes marinus are a crucial forage fish species in the North Sea, transferring zooplankton energy to higher trophic levels. However, there has been a sustained decline in sandeel abundance in the northwestern North Sea since 2000. Here we use field data to analyze year-to-year changes in A. marinus growth rate between 1997 and 2009 and assess whether variation in growth rate corresponded with variation in abundance. The signature of the reduction in abundance between 2000 and 2009 was a decline in age 1 sandeels, while no other age class declined. Analysis of age-length data showed that the decline in abundance coincided with a period of low growth. Growth performance indexes were correlated with zooplankton and phytoplankton biomass but not temperature. Further, we observed a significant correlation between larval growth rate and 0-group sandeel length during a period when hatch dates were relatively fixed; suggesting recent changes in length were influenced by food availability.